THE INFLUENCE OF HALAL AWARENESS, EWOM TOWARDS INTENTION TO BUY HALAL COSMETICS: THE ROLE OF MEDIATION ATTITUDE - Lily Purwianti (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
Indonesia is a country with the largest population of Muslims, so the use of halal products is an opportunity for halal product producers. This study aims to examine the effect of Halal Awareness and e-WOM on the intention to buy halal cosmetics and the role of mediation Attitude. The sample of this research is Muslim women in Batam City who know about halal cosmetics. The number of samples is 388 respondents and uses smart PLS for data analysis. The results of this study are halal awareness and e-WOM affect the Intention to buy halal cosmetics. Surprisingly from other research results, attitude acts as a mediation between halal awareness and e-WOM on the Intention to buy halal cosmetics.